2013
DOI: 10.21273/jashs.138.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Application of an Analog of 9, 10-ketol-octadecadienoic acid (KODA), Affected Flower Bud Formation and MdTFL1 and MdFT1 Gene Expressions in Apple Buds under Heavy-crop and Shade Conditions

Abstract: Changes of endogenous 9, 10-ketol-octadecadienoic acid (KODA) concentrations, which is synthesized from linolenic acid by 9-lipoxygenase, were analyzed in apple [Malus ×sylvestris (L.) Mill. var. domestica (Borkh.) Mansf.] buds. In addition, the effects of 15, 16-chloro, hydroxy-9-hydroxy-10-oxo-12(Z)-octadecenoic acid (CKODA) application, which is an analog of KODA, on flower bud formation and the expression of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Meristem fate in apple buds is regulated by genetic, physiological, and chemical signals. Exogenous application of compounds including GA 4 (Looney et al, 1985), NAA (Harley et al, 1958;McArtney et al, 2007), ethylene (McArtney et al, 2007Williams, 1972), and an analog of 9,10-ketol-octadecadienoic acid (Kittikorn et al, 2013) exhibits florigenic activity in apple. In this work, we have shown that applying NAA during the period when meristems are normally doming promotes flower bud formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meristem fate in apple buds is regulated by genetic, physiological, and chemical signals. Exogenous application of compounds including GA 4 (Looney et al, 1985), NAA (Harley et al, 1958;McArtney et al, 2007), ethylene (McArtney et al, 2007Williams, 1972), and an analog of 9,10-ketol-octadecadienoic acid (Kittikorn et al, 2013) exhibits florigenic activity in apple. In this work, we have shown that applying NAA during the period when meristems are normally doming promotes flower bud formation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has revealed that the proteins encoded by FLOWERING LOCUS T (FT) in Arabidopsis and its orthologs in other plant species is a key component of florigen (Corbesier et al, 2007;Lin et al, 2007;Tamaki et al, 2007;Zeevart, 2006). Kittikorn et al (2013) reported that application of 9,10-ketol-octadecadienoic acid increased MdFT1 expression and flower bud formation in apple. Because NAA sprays at different times during the growing season are florigenic, analysis of gene expression after NAA treatments may provide an alternative approach to studying the endogenous control of flower bud formation in apple.…”
Section: Resultsmentioning
confidence: 99%
“…In some plants, the intracellular concentration of KODA changes in response to environmental changes, or according to the developmental stage ( Yokoyama et al , 2000 , 2005 ). The application of KODA was initially shown to promote flowering in various plants such as Lemna paucicostata ( Yokoyama et al , 2000 ), Malus pamila ( Kittikorn et al , 2011 , 2013 ), Citrus unshiu ( Nakajima et al , 2016 ), and Pharbitis nil ( Ono et al , 2013 ). KODA also promotes rooting ( Kawakami et al , 2015 ), re-shooting after dormancy ( Sakamoto et al , 2010 , 2012 ; Nakajima et al , 2016 ), and it also increases wheat yield ( Haque et al , 2016 ) and enhances the resistance of certain herbaceous plants to pathogens ( Endo et al , 2013 ; Wang et al , 2016 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%